Preparation method of flame-retardant adhesive and application of flame-retardant adhesive in self-adhesive label

By using a combination of self-healing monomer and grafted starch in the self-adhesive label, a stable carbonization layer and water evaporation mechanism is formed, which solves the problem of flammability of adhesives, significantly improves the flame retardant performance and bonding strength, and prevents fire. The accident occurred.

CN119193011APending Publication Date: 2024-12-27JIANGSU JINDA PACKAGING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411459110.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The flammability of adhesives in existing self-adhesive labels leads to the risk of fire accidents, and their flame retardant properties are insufficient to effectively prevent the material from burning.

Method used

The repair monomer was prepared by catalyzing 4-vinylbenzene boric acid into a six-membered ring and reacting with dimethylphosphorus and 1,2-epoxychlorobutane, and corn starch was used with methyl methacrylate and 3- The reaction of methyl methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol to produce grafted starch, and the mixture is mixed to produce flame retardant adhesive, which is produced by the reaction of phosphorus and boron oxide hexacycles. Self-healing and anti-aging effects, forming a stable carbonization layer and water evaporation to flame retardant.

Benefits of technology

The flame retardant capacity of the adhesive is significantly improved, and the generated polymetaphosphoric acid and water evaporation mechanism prevents the material from burning, and enhances the viscosity and bonding strength, effectively preventing the occurrence of fire accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091352810000081
    Figure BDA0005091352810000081
Patent Text Reader

Abstract

The invention discloses a preparation method of a flame-retardant adhesive and application of the flame-retardant adhesive in a self-adhesive label, and relates to the technical field of adhesives. When the flame-retardant adhesive is prepared, 4-vinylphenylboronic acid is catalyzed into a six-membered ring, and then the six-membered ring sequentially reacts with dimethyl phosphorus and 1, 2-epoxy chlorobutane to prepare a self-repairing monomer; the preparation method comprises the following steps: reacting corn starch with methyl methacrylate, methyl 3-methyl-3-butenoate and 2, 6-di-tert-butyl-4-vinylphenol, so as to obtain grafted starch; and mixing the grafted starch with a self-repairing monomer to prepare the flame-retardant adhesive. The flame-retardant adhesive prepared by the preparation method disclosed by the invention has good anti-aging and self-repairing capabilities and relatively good viscosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a method for preparing a flame retardant adhesive and application of the flame retardant adhesive in a self-adhesive label. Background Art

[0002] my country's self-adhesive label industry has maintained sustained rapid growth in recent years. Self-adhesive labels have been widely used in the daily chemical industry. At present, most of the self-adhesive label materials on the domestic market are used in daily products. Self-adhesive labels will continue to maintain rapid growth in the daily chemical industry, be more widely used, and label materials will also develop to a higher level.

[0003] Industry insiders predict that in the next few years, the demand for self-adhesive labels in the daily chemical industry, electronic and electrical industry, pharmaceutical industry and logistics industry will grow greatly. The main components of the basic structure of self-adhesive labels are surface material, adhesive, silicon coating layer and base paper. Among them, adhesive is a very important component of self-adhesive labels. Adhesive has a certain flammability, so fire accidents may occur when encountering open flames or high temperatures. Therefore, this article introduces a flame retardant adhesive. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a flame retardant adhesive and a lithium ion battery to solve the problems existing in the prior art.

[0005] A method for preparing a flame retardant adhesive, the method for preparing the flame retardant adhesive comprising mixing grafted starch with a self-repairing monomer;

[0006] The self-repairing monomer is prepared by catalyzing 4-vinylbenzene boronic acid into a six-membered ring and then reacting it with dimethyl phosphine and 1,2-epoxychlorobutane in sequence;

[0007] The grafted starch is prepared by reacting corn starch with methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol.

[0008] According to the method for preparing a flame retardant adhesive according to claim 1, the method for preparing the flame retardant adhesive mainly comprises the following preparation steps:

[0009] (1) mixing the olefin-containing boroxane with dimethyl phosphine in a molar ratio of 1:3, placing in a high-pressure reactor, reacting at 115-125° C. for 10-12 hours, and obtaining the phosphorus-containing boroxane; mixing the phosphorus-containing boroxane with sodium iodide in a mass ratio of 80-100:1, immersing in acetone, adding an equal molar amount of 1,2-epoxychlorobutane with dimethyl phosphine at 35-45° C. under nitrogen protection, reacting for 46-50 hours, and drying at 50-60° C. for 12-14 hours, and obtaining the self-healing monomer;

[0010] (2) Take 1 part of corn starch, 3.5-4.5 parts of deionized water, 0.003-0.005 parts of hydrochloric acid solution, 3.5-4.5 parts of polyvinyl alcohol solution, 0.01-0.03 parts of potassium persulfate, 0.1-0.2 parts of methyl methacrylate, 0.1-0.2 parts of methyl 3-methyl-3-butenoate, 0.05-0.07 parts of 2,6-di-tert-butyl-4-vinylphenol and 0.0003-0.0005 parts of urea according to mass fraction; mix the corn starch, deionized water and hydrochloric acid solution, and heat at 200-30 The mixture was stirred at 0 r / min for 40 to 60 minutes, the pH value was adjusted to 5 to 6 with a sodium hydroxide solution, and then a polyvinyl alcohol solution was added, the temperature was raised to 70 to 90°C, and the stirring was continued for 25 to 35 minutes. Potassium persulfate, methyl methacrylate, 3-methyl-3-butenoic acid methyl ester and 2,6-di-tert-butyl-4-vinylphenol were added, and the stirring was continued for 2 to 3 hours. The mixture was heated to 80 to 90°C, and the stirring was continued for 5 to 7 hours. The mixture was cooled to 60 to 70°C, urea was added, and the stirring was continued for 30 to 50 minutes. The stirring was stopped, and the mixture was taken out to obtain the grafted starch.

[0011] (3) The grafted starch and the self-healing monomer are mixed evenly in a mass ratio of 1:0.2-0.3, and allowed to stand at room temperature for 3-5 days to obtain a flame retardant adhesive.

[0012] As an optimization, the hexacyclic olefin-containing borane in step (1) is prepared by mixing 4-vinylbenzeneboronic acid and thionyl chloride in a mass ratio of 1:4-6, stirring at 70-90°C and 200-300 r / min for 11-13 hours, and drying at 70-74°C for 10-12 hours.

[0013] As an optimization, the hydrochloric acid solution in step (2) is prepared by uniformly mixing hydrogen chloride and deionized water in a mass ratio of 1:2.1 to 2.2.

[0014] As an optimization, the polyvinyl alcohol solution in step (2) is prepared by uniformly mixing polyvinyl alcohol and deionized water in a mass ratio of 1:18 to 20.

[0015] As an optimization, the sodium hydroxide solution in step (2) is prepared by uniformly mixing sodium hydroxide and deionized water in a mass ratio of 1:8 to 10.

[0016] A use of a flame retardant adhesive prepared by the method for preparing a flame retardant adhesive according to any one of claims 1 to 6 in a self-adhesive label.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0018] When preparing the flame retardant adhesive, the present invention comprises the following steps: catalyzing 4-vinylbenzene boronic acid into a six-membered ring and then reacting the six-membered ring with dimethyl phosphine and 1,2-epoxychlorobutane in sequence to obtain a self-repairing monomer; reacting corn starch with methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol to obtain grafted starch; and mixing the grafted starch with the self-repairing monomer to obtain the flame retardant adhesive.

[0019] First, 4-vinylbenzene boronic acid is catalyzed into a six-membered ring and then reacted with dimethyl phosphorus and 1,2-epoxychlorobutane in sequence to obtain a self-repairing monomer. The phosphorus in the self-repairing monomer can produce phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction and thus slow down the combustion. During the combustion process, a structurally stable and non-volatile polymetaphosphoric acid can be generated. Polymetaphosphoric acid has a strong dehydration effect. During the heating process, the polymer is carbonized into a dense and flame-retardant carbonized layer. The carbonized layer covers the surface of the polymer, isolating the bottom material from contact with external oxygen and hindering External heat is transferred to the base material, thereby effectively preventing further pyrolysis of the material and terminating the combustion of the material, thereby improving the flame retardancy of the material; the hexacyclic boroxide in the self-healing monomer breaks and can react with the hydroxyl group on the starch to form a ring again, thereby achieving a self-healing effect. The hexacyclic boroxide melts during combustion, which can absorb part of the heat and cover the surface of the polymer to isolate the combustible from oxygen. It can also release bound water at high temperature, and the evaporation of water cools the material, and changes the thermal decomposition pathway of the combustible, thereby reducing the generation of combustible gases and achieving a flame retardant effect.

[0020] Secondly, corn starch is reacted with methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol to obtain grafted starch; the grafted starch is mixed with a self-repairing monomer to obtain a flame retardant adhesive, the starch is first hydrolyzed with hydrochloric acid to break the starch molecular chain and reduce the degree of polymerization of the starch macromolecules, and then methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol are grafted onto the starch molecular chain by potassium persulfate initiation. 2,6-di-tert-butyl-4-vinylphenol can be As a free radical scavenger, it can convert peroxy radicals into hydroperoxides. The generated phenoxy radicals continue to react with peroxy radicals in different ways to generate non-radical products, achieving anti-aging effects. Graft modification is a method of modifying starch adhesives. The viscosity and bonding strength of the adhesives prepared by this method are significantly improved. The adhesives are rich in hydroxyl and ester groups, which are easy to form hydrogen bonds, improve the crosslinking degree and chemical stability of the copolymers, enhance the intermolecular forces, make the structure of the latex particles more compact, and reduce the particle size, thereby increasing the viscosity of the adhesive. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] A method for preparing a flame retardant adhesive mainly comprises the following preparation steps:

[0024] (1) mixing the olefin-containing boroxane with dimethyl phosphine in a molar ratio of 1:3, placing in a high-pressure reactor, reacting at 115°C for 10 hours, and obtaining the phosphorus-containing boroxane; mixing the phosphorus-containing boroxane with sodium iodide in a mass ratio of 80:1, immersing in acetone, adding an equal molar amount of 1,2-epoxychlorobutane with dimethyl phosphine at 35°C under nitrogen protection, reacting for 46 hours, and drying at 50°C for 12 hours to obtain a self-healing monomer;

[0025] (2) Take 1 part of corn starch, 3.5 parts of deionized water, 0.003 parts of hydrochloric acid solution, 3.5 parts of polyvinyl alcohol solution, 0.01 parts of potassium persulfate, 0.1 parts of methyl methacrylate, 0.1 parts of methyl 3-methyl-3-butenoate, 0.05 parts of 2,6-di-tert-butyl-4-vinylphenol and 0.0003 parts of urea according to mass fraction; mix the corn starch, deionized water and hydrochloric acid solution, stir at 200 r / min for 40 minutes, adjust the pH to 5 with sodium hydroxide solution, add polyvinyl alcohol solution, heat to 70°C, continue stirring for 25 minutes, add potassium persulfate, methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol, continue stirring for 2 hours, heat to 80°C, continue stirring for 5 hours, cool to 60°C, add urea, continue stirring for 30 minutes, stop stirring, take out, and obtain grafted starch;

[0026] (3) The grafted starch and the self-healing monomer were mixed evenly in a mass ratio of 1:0.2 and allowed to stand at room temperature for 3 days to obtain a flame retardant adhesive.

[0027] Example 2

[0028] A method for preparing a flame retardant adhesive mainly comprises the following preparation steps:

[0029] (1) mixing the olefin-containing boroxane with dimethyl phosphine in a molar ratio of 1:3, placing in a high-pressure reactor, reacting at 120°C for 11 hours, and obtaining the phosphorus-containing boroxane; mixing the phosphorus-containing boroxane with sodium iodide in a mass ratio of 90:1, immersing in acetone, adding an equal molar amount of 1,2-epoxychlorobutane with dimethyl phosphine at 40°C under nitrogen protection, reacting for 48 hours, and drying at 55°C for 13 hours to obtain a self-healing monomer;

[0030] (2) Take 1 part of corn starch, 4 parts of deionized water, 0.004 parts of hydrochloric acid solution, 4 parts of polyvinyl alcohol solution, 0.02 parts of potassium persulfate, 0.15 parts of methyl methacrylate, 0.15 parts of methyl 3-methyl-3-butenoate, 0.06 parts of 2,6-di-tert-butyl-4-vinylphenol and 0.0004 parts of urea according to mass fraction; mix the corn starch, deionized water and hydrochloric acid solution, stir at 250 r / min for 50 minutes, adjust the pH to 5.5 with sodium hydroxide solution, add polyvinyl alcohol solution, heat to 80°C, continue stirring for 30 minutes, add potassium persulfate, methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol, continue stirring for 2.5 hours, heat to 85°C, continue stirring for 6 hours, cool to 65°C, add urea, continue stirring for 40 minutes, stop stirring, take out, and obtain grafted starch;

[0031] (3) The grafted starch and the self-healing monomer were mixed evenly in a mass ratio of 1:0.25 and allowed to stand at room temperature for 4 days to obtain a flame retardant adhesive.

[0032] Example 3

[0033] A method for preparing a flame retardant adhesive mainly comprises the following preparation steps:

[0034] (1) mixing the olefin-containing boroxane with dimethyl phosphine in a molar ratio of 1:3, placing in a high-pressure reactor, reacting at 125°C for 12 hours, and obtaining the phosphorus-containing boroxane; mixing the phosphorus-containing boroxane with sodium iodide in a mass ratio of 100:1, immersing in acetone, adding an equal molar amount of 1,2-epoxychlorobutane with dimethyl phosphine at 45°C under nitrogen protection, reacting for 50 hours, and drying at 60°C for 14 hours to obtain a self-healing monomer;

[0035] (2) Take 1 part of corn starch, 4.5 parts of deionized water, 0.005 parts of hydrochloric acid solution, 4.5 parts of polyvinyl alcohol solution, 0.03 parts of potassium persulfate, 0.2 parts of methyl methacrylate, 0.2 parts of methyl 3-methyl-3-butenoate, 0.07 parts of 2,6-di-tert-butyl-4-vinylphenol and 0.0005 parts of urea according to mass fraction; mix the corn starch, deionized water and hydrochloric acid solution, stir at 300 r / min for 60 minutes, adjust the pH to 6 with sodium hydroxide solution, add polyvinyl alcohol solution, heat to 90°C, continue stirring for 35 minutes, add potassium persulfate, methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol, continue stirring for 3 hours, heat to 90°C, continue stirring for 7 hours, cool to 70°C, add urea, continue stirring for 50 minutes, stop stirring, take out, and obtain grafted starch;

[0036] (3) The grafted starch and the self-healing monomer were mixed evenly in a mass ratio of 1:0.3 and allowed to stand at room temperature for 5 days to obtain a flame retardant adhesive.

[0037] Comparative Example 1

[0038] A method for preparing a flame retardant adhesive mainly comprises the following preparation steps:

[0039] (1) Triallyl borane and dimethyl phosphine were mixed in a molar ratio of 1:3, placed in a high-pressure reactor, and reacted at 120° C. for 11 hours to obtain a phosphorus-containing monomer; the phosphorus-containing monomer was mixed with sodium iodide in a mass ratio of 90:1, immersed in acetone, and an equal molar amount of 1,2-epoxychlorobutane was added to dimethyl phosphine at 40° C. under nitrogen protection, reacted for 48 hours, and dried at 55° C. for 13 hours to obtain a flame retardant monomer;

[0040] (2) Take 1 part of corn starch, 4 parts of deionized water, 0.004 parts of hydrochloric acid solution, 4 parts of polyvinyl alcohol solution, 0.02 parts of potassium persulfate, 0.15 parts of methyl methacrylate, 0.15 parts of methyl 3-methyl-3-butenoate, 0.06 parts of 2,6-di-tert-butyl-4-vinylphenol and 0.0004 parts of urea according to mass fraction; mix the corn starch, deionized water and hydrochloric acid solution, stir at 250 r / min for 50 minutes, adjust the pH to 5.5 with sodium hydroxide solution, add polyvinyl alcohol solution, heat to 80°C, continue stirring for 30 minutes, add potassium persulfate, methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol, continue stirring for 2.5 hours, heat to 85°C, continue stirring for 6 hours, cool to 65°C, add urea, continue stirring for 40 minutes, stop stirring, take out, and obtain grafted starch;

[0041] (3) The grafted starch and the flame retardant monomer were mixed evenly in a mass ratio of 1:0.25 and allowed to stand at room temperature for 4 days to obtain a flame retardant adhesive.

[0042] Comparative Example 2

[0043] A method for preparing a flame retardant adhesive mainly comprises the following preparation steps:

[0044] (1) Take 1 part of corn starch, 4 parts of deionized water, 0.004 parts of hydrochloric acid solution, 4 parts of polyvinyl alcohol solution, 0.02 parts of potassium persulfate, 0.15 parts of methyl methacrylate, 0.15 parts of methyl 3-methyl-3-butenoate, 0.06 parts of 2,6-di-tert-butyl-4-vinylphenol and 0.0004 parts of urea according to mass fraction; mix the corn starch, deionized water and hydrochloric acid solution, stir at 250 r / min for 50 minutes, adjust the pH to 5.5 with sodium hydroxide solution, add polyvinyl alcohol solution, heat to 80°C, continue stirring for 30 minutes, add potassium persulfate, methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol, continue stirring for 2.5 hours, heat to 85°C, continue stirring for 6 hours, cool to 65°C, add urea, continue stirring for 40 minutes, stop stirring, take out, and prepare an adhesive;

[0045] Comparative Example 3

[0046] A method for preparing a flame retardant adhesive mainly comprises the following preparation steps:

[0047] (1) mixing the olefin-containing boroxane with dimethyl phosphine in a molar ratio of 1:3, placing in a high-pressure reactor, reacting at 120°C for 11 hours, and obtaining the phosphorus-containing boroxane; mixing the phosphorus-containing boroxane with sodium iodide in a mass ratio of 90:1, immersing in acetone, adding an equal molar amount of 1,2-epoxychlorobutane with dimethyl phosphine at 40°C under nitrogen protection, reacting for 48 hours, and drying at 55°C for 13 hours to obtain a self-healing monomer;

[0048] (2) Take 1 part of corn starch, 4 parts of deionized water, 0.004 parts of hydrochloric acid solution, 4 parts of polyvinyl alcohol solution, 0.02 parts of potassium persulfate, 0.15 parts of methyl methacrylate, 0.15 parts of 3-methyl-3-butenoic acid methyl ester and 0.0004 parts of urea according to mass fraction; mix the corn starch, deionized water and hydrochloric acid solution, stir at 250r / min for 50min, adjust the pH to 5.5 with sodium hydroxide solution, add polyvinyl alcohol solution, heat to 80°C, continue stirring for 30min, add potassium persulfate, methyl methacrylate, 3-methyl-3-butenoic acid methyl ester and 2,6-di-tert-butyl-4-vinylphenol, continue stirring for 2.5h, heat to 85°C, continue stirring for 6h, cool to 65°C, add urea, continue stirring for 40min, stop stirring, take out, and obtain grafted starch;

[0049] (3) The grafted starch and the self-healing monomer were mixed evenly in a mass ratio of 1:0.25 and allowed to stand at room temperature for 4 days to obtain a flame retardant adhesive.

[0050] Comparative Example 4

[0051] A method for preparing a flame retardant adhesive mainly comprises the following preparation steps:

[0052] (1) mixing the olefin-containing boroxane with dimethyl phosphine in a molar ratio of 1:3, placing in a high-pressure reactor, reacting at 120°C for 11 hours, and obtaining the phosphorus-containing boroxane; mixing the phosphorus-containing boroxane with sodium iodide in a mass ratio of 90:1, immersing in acetone, adding an equal molar amount of 1,2-epoxychlorobutane with dimethyl phosphine at 40°C under nitrogen protection, reacting for 48 hours, and drying at 55°C for 13 hours to obtain a self-healing monomer;

[0053] (2) Corn starch and self-healing monomer were mixed evenly in a mass ratio of 1:0.25 and allowed to stand at room temperature for 4 days to obtain a flame retardant adhesive.

[0054] Test Example 1

[0055] Adhesion test, aging resistance, self-healing test

[0056] Viscosity test: The viscosity of the prepared adhesive was measured on a NDJ-79 rotational viscometer;

[0057] Adhesive strength test: refer to the national standard GB / T7124-2008, glue 2×5cm paperboards together with adhesive, dry the paper sample in an electric constant temperature blast drying oven, connect the HP digital push-pull force gauge to the computer, start the test, slowly rotate the force gauge and observe the curve trend until the two paper pieces separate, then stop the test and record the maximum tension;

[0058] Anti-aging test: The adhesive sample is aged for three days at a temperature of 70°C and a humidity of 100%, and the bonding strength test is performed again, and the maximum tensile force after aging is recorded;

[0059] Self-repair test: After the adhesive was repeatedly pasted on a 2×5 cm cardboard for 8 times, it was left at 80°C for 24 hours, cooled to room temperature, and the bonding strength test was performed again, which was recorded as the maximum tensile force after self-repair. The results are shown in Table 1.

[0060] Table 1

[0061]

[0062] From the comparison of the experimental data in Table 1, it can be found that the flame retardant adhesive prepared by the present invention has higher viscosity and good self-repairing and anti-aging capabilities.

[0063] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the maximum tensile force after self-repair of Examples 1, 2, 3 is greater than that of Comparative Example 1, indicating that the hexacyclic boron oxide in the self-repairing monomer is broken and can react with the hydroxyl group on the starch to form a ring again, thereby achieving a self-repairing effect;

[0064] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the maximum tensile force after aging of Examples 1, 2, 3 is greater than that of Comparative Example 3, indicating that 2,6-di-tert-butyl-4-vinylphenol can be used as a free radical scavenger to convert peroxy radicals into hydroperoxides, and the generated phenoxy radicals continue to react with peroxy radicals in different ways to generate non-radical products, thereby achieving an anti-aging effect;

[0065] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the viscosity and maximum tensile force of Examples 1, 2, 3 are greater than those of Comparative Example 4, which shows that grafting modification is a method of modifying starch adhesives, and the viscosity and bonding strength of the adhesives prepared by this method will be significantly improved.

[0066] Test Example 2

[0067] Flame retardancy test

[0068] The limiting oxygen index was tested according to GB / T2406 test standard. The results are shown in Table 2.

[0069] Table 2

[0070] Limiting oxygen index Example 1 33.6% Example 2 33.3% Example 3 33.5% Comparative Example 1 32.0% Comparative Example 2 28.7% Comparative Example 3 33.4% Comparative Example 4 33.1%

[0071] From the comparison of the experimental data in Table 2, it can be found that the flame retardant adhesive prepared by the present invention has good flame retardant ability.

[0072] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 2, it can be found that the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 1, which indicates that the hexacyclic boron oxide in the self-repairing monomer is broken and can react with the hydroxyl group on the starch to form a ring again, thereby achieving a self-repairing effect. Moreover, the hexacyclic boron oxide melts during combustion, absorbs part of the heat, and covers the surface of the polymer, isolating the combustible from contact with oxygen. It can also release bound water at high temperature, and the evaporation of the water cools the material, and changes the thermal decomposition pathway of the combustible, thereby reducing the generation of combustible gas, achieving a flame retardant effect, and increasing the limiting oxygen index.

[0073] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the limiting oxygen index of Examples 1, 2, 3 is higher than that of Comparative Example 2, which shows that the phosphorus in the self-repairing monomer can produce phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction and thus slow down the combustion, and can generate polyphosphoric acid with stable structure and non-volatile structure during the combustion process. Polyphosphoric acid has a strong dehydration effect, and during the heating process, the polymer is carbonized into a dense and flame-retardant carbonized layer. The carbonized layer covers the surface of the polymer, isolates the bottom material from contact with external oxygen, and hinders the transfer of external heat to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, improving the flame retardant ability of the material, and increasing the limiting oxygen index.

[0074] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a flame retardant adhesive, characterized in that: The flame retardant adhesive is prepared by mixing grafted starch with a self-repairing monomer; The self-repairing monomer is prepared by catalyzing 4-vinylbenzene boronic acid into a six-membered ring and then reacting it with dimethyl phosphine and 1,2-epoxychlorobutane in sequence; The grafted starch is prepared by reacting corn starch with methyl methacrylate, methyl 3-methyl-3-butenoate and 2,6-di-tert-butyl-4-vinylphenol.

2. The method for preparing a flame retardant adhesive according to claim 1, characterized in that: The preparation method of the flame retardant adhesive mainly includes the following preparation steps: (1) mixing the olefin-containing boroxane with dimethyl phosphine in a molar ratio of 1:3, placing in a high-pressure reactor, reacting at 115-125° C. for 10-12 hours, and obtaining the phosphorus-containing boroxane; mixing the phosphorus-containing boroxane with sodium iodide in a mass ratio of 80-100:1, immersing in acetone, adding an equal molar amount of 1,2-epoxychlorobutane with dimethyl phosphine at 35-45° C. under nitrogen protection, reacting for 46-50 hours, and drying at 50-60° C. for 12-14 hours, and obtaining the self-healing monomer; (2) Take 1 part of corn starch, 3.5-4.5 parts of deionized water, 0.003-0.005 parts of hydrochloric acid solution, 3.5-4.5 parts of polyvinyl alcohol solution, 0.01-0.03 parts of potassium persulfate, 0.1-0.2 parts of methyl methacrylate, 0.1-0.2 parts of methyl 3-methyl-3-butenoate, 0.05-0.07 parts of 2,6-di-tert-butyl-4-vinylphenol and 0.0003-0.0005 parts of urea according to mass fraction; mix the corn starch, deionized water and hydrochloric acid solution, and heat at 200-30 The mixture was stirred at 0 r / min for 40 to 60 minutes, the pH value was adjusted to 5 to 6 with a sodium hydroxide solution, and then a polyvinyl alcohol solution was added, the temperature was raised to 70 to 90°C, and the stirring was continued for 25 to 35 minutes. Potassium persulfate, methyl methacrylate, 3-methyl-3-butenoic acid methyl ester and 2,6-di-tert-butyl-4-vinylphenol were added, and the stirring was continued for 2 to 3 hours. The mixture was heated to 80 to 90°C, and the stirring was continued for 5 to 7 hours. The mixture was cooled to 60 to 70°C, urea was added, and the stirring was continued for 30 to 50 minutes. The stirring was stopped, and the mixture was taken out to obtain the grafted starch. (3) The grafted starch and the self-healing monomer are mixed evenly in a mass ratio of 1:0.2-0.3, and allowed to stand at room temperature for 3-5 days to obtain a flame retardant adhesive.

3. The method for preparing a flame retardant adhesive according to claim 2, characterized in that: The olefin-containing hexacyclic borane in step (1) is prepared by mixing 4-vinylbenzeneboronic acid and thionyl chloride in a mass ratio of 1:4-6, stirring at 70-90° C. and 200-300 r / min for 11-13 hours, and drying at 70-74° C. for 10-12 hours.

4. The method for preparing a flame retardant adhesive according to claim 2, characterized in that: The hydrochloric acid solution in step (2) is prepared by uniformly mixing hydrogen chloride and deionized water in a mass ratio of 1:2.1 to 2.

2.

5. The method for preparing a flame retardant adhesive according to claim 2, characterized in that: The polyvinyl alcohol solution in step (2) is prepared by uniformly mixing polyvinyl alcohol and deionized water in a mass ratio of 1:18-20.

6. The method for preparing a flame retardant adhesive according to claim 2, characterized in that: The sodium hydroxide solution in step (2) is prepared by uniformly mixing sodium hydroxide and deionized water in a mass ratio of 1:8 to 10.

7. Use of the flame retardant adhesive prepared by the method for preparing the flame retardant adhesive according to any one of claims 1 to 6 in a self-adhesive label.